Cardiac resynchronization therapy: pre and post pacemaker implantation issues - Chin, Ashley; Okreglicki, Andrzej (SA Heart Journal, 2017)
Cardiac resynchronization therapy (CRT) has been shown to improve clinical outcomes in patients with systolic heart failure. However, up to one-third of patients do not benefit from CRT. Selection of appropriate patients with attention to heart failure management and optimization of pacemaker settings post-implantation will ensure the best chance of a favorable response to CRT. This article will review the current indications for CRT and provide recommendations regarding optimization and follow-up of patients with CRT.